Study on the Effect of H2 Addition to N2 on EEDF and Electron Transport Coefficients - Jassim, Mustafa. K.; Jawad, Enas A.; Alsaide, Jamal K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
In this paper, we calculate the electron energy distribution function (EEDF) and transport parameters including the electron mean energy, mobility, drift velocity and diffusion coefficient for the gas mixtures of the H2 and N2 using the EEDF program. It is concentrated on the effect of assorted concentrations of the mixtures on the EEDF and the electron transport coefficients. The work exhibits the variation amongst the different mixtures on the EEDF and the transport parameter. The results are graphically offered and discussed. In this concept, it is shown that for each mixture has a specific impact on EEDF and the transport parameter. The important of this study comes from the usage of these mixtures in DC (direct current) glow discharge. These results are salutary to detect the best gas mixtures to reach proper transport parameters.